An effect of inhibitory load in children while keeping working memory load constant - Diamond, Adele; Wright, Andy (Frontiers in Psychology, 2014)
People are slower and more error-prone when the correct response is away from a stimulus (incongruent) than when it is towards a stimulus (congruent). Two reasons for this are possible. It could be caused by the requirement to inhibit the prepotent tendency to respond toward a stimulus, or by the order of task presentation causing difficulty switching from one rule to another especially if one does not efficiently delete the first rule from active working memory. This experiment (with 96 children [49 girls] 6-10 years old) used the hearts and flowers task (a hybrid combining elements of Simon and Spatial Stroop tasks used in several studies with children: Davidson et al., 2006; Diamond et al., 2007; Edgin et al., 2010; Zaitchik et al., 2013) to differentiate between those two possibilities by counterbalancing order of task presentation. Half the children were presented with the congruent block first (the traditional order for the task, where the rule is to “press on the same side as the stimulus”) and half with incongruent trials first (with the rule “press on the side opposite the stimulus”). The results, which were the same regardless of task order, clearly show that the increased inhibitory control demand is responsible for children’s decreased accuracy and slower responses in the incongruent block. Worse performance on incongruent trials when they came first cannot be accounted for by inefficient clearing of working memory or by task-switching accounts. Since working memory demands are no greater on the incongruent block when it is presented first than on the congruent block when presented first, yet performance was worse, results here indicate that increasing inhibitory demands alone is sufficient to impair children’s performance in the face of no change in working memory demands, suggesting that inhibition must be a separate mental function from working memory.